An Analysis of Illocutionary Acts in Beauty Product Advertisements in Television Broadcast - Saputri, Nurul Intan; Hidayat, Didin Nuruddin; Alek, Alek; Eviyuliwati, Ismalianing (Yayasan Visi Intan Permata, 2021)
Nowadays, advertising is no stranger to the wider community. We can commonly find advertisements through several media such as television, radio, magazines, billboards, and even YouTube. The present study attempts to investigate the type of illocutionary acts used in beauty product advertisement utterances in television broadcasts. The significance is to enrich the literature on speech acts used by advertisers, especially illocutionary acts in beauty products. This research's main data were several advertisements utterances of beauty products, such as shampoo advertisements, cosmetic advertisements, facial wash advertisements, and other related beauty advertisement products. Further, the data were described by a descriptive study.Â In addition, data were gathered by downloading the advertisement from YouTube and taking note the conversation to analyse the utterances used in the advertisements. Furthermore, the data were analysed based on context advertisement utterances in the form of conversations on television broadcast and classified the utterances using the theory proposed by Searle about types of illocutionary act. There are five types of illocutionary by Searle: declarative, representative, expressive, directive, and commissive. Above all, the findings showed that the assertive function dominates in beauty advertisements and commissive is the type rarely used in beauty product advertisements.